Future Directions in Research on Beaked Whales - Hooker, Sascha K.; De Soto, Natacha Aguilar; Baird, Robin W.; Carroll, Emma L.; Claridge, Diane; Feyrer, Laura; Miller, Patrick J. O.; Onoufriou, Aubrie; Schorr, Greg; Siegal, Eilidh; Whitehead, Hal (Frontiers in Marine Science, 2019)
Until the 1990s, beaked whales were one of the least understood groups of large mammals. Information on northern bottlenose whales (Hyperoodon ampullatus) and Baird’s beaked whales (Berardius bairdii) was available from data collected during whaling, however, little information existed on the smaller species other than occasional data gleaned from beach-cast animals. Recent research advances have been plentiful. Increasing global survey effort, together with morphometric and genetic analyses have shown at least 22 species in this group. Longitudinal field studies of at least four species (H. ampullatus, B. bairdii, Ziphius cavirostris, Mesoplodon densirostris) have become established over the last three decades. Several long-term studies support photo-identification catalogues providing insights into life history, social structure and population size. Tag-based efforts looking at diving, movements and acoustics have provided detail on individual behaviour as well as population structure and ranges. Passive acoustic monitoring has allowed long-term and seasonal monitoring of populations. Genetic studies have uncovered cryptic species and revealed contrasting patterns of genetic diversity and connectivity amongst the few species examined. Conservation concern for these species was sparked by mass strandings coincident with military mid-frequency sonar use. Fat and gas emboli have been symptomatic indicators of mortalities related to sonar exposure, suggesting that their vulnerability stems from the physiological exertion of extreme diving for medium-sized whales. Behavioural response experiments have now shown that beaked whales appear to cease foraging and delay their return to foraging and/or leave the area in association with exposure to mid-frequency signals at low acoustic levels. Future priorities for these species will be to (1) continue field-studies to better understand smaller-scale habitat use, vital rates and social structure; (2) develop better detection methods for larger-scale survey work; (3) improve methodology for monitoring energetics, individual body condition and health; (4) develop tools to better understand physiology; (5) use recent genetic advances with improved sample databanks to re-examine global and local beaked whale relationships; (6) further quantify anthropogenic impacts (both sonar and other noise) and their population consequences (7) apply acquired data for realistic mitigation of sonar and other anthropogenic impacts for beaked whale conservation.